2007
DOI: 10.1111/j.1600-0560.2007.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Src‐family tyrosine kinases in hyperproliferative epidermal disorders

Abstract: This study shows increased staining of activated SFKs in human biopsy specimens of psoriasis and cutaneous neoplasia. These data provide direct evidence for increased activation of SFKs in the pathogenesis of hyperproliferative epidermal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…SFK are known oncogenes 47 and can be downregulated by Srcasm 48. Increased activation of SFK and decreased Srcasm levels were reported in CSCC compared with unremarkable epidermis 27, 49, 50. It was later reported that the transgenic mice with elevated SFK activity spontaneously formed CSCC, and cutaneous neoplasia can be markedly inhibited by increasing Srcasm levels 27.…”
Section: Notch Signaling In Cutaneous Squamous Cell Carcinoma (Cscc)mentioning
confidence: 99%
“…SFK are known oncogenes 47 and can be downregulated by Srcasm 48. Increased activation of SFK and decreased Srcasm levels were reported in CSCC compared with unremarkable epidermis 27, 49, 50. It was later reported that the transgenic mice with elevated SFK activity spontaneously formed CSCC, and cutaneous neoplasia can be markedly inhibited by increasing Srcasm levels 27.…”
Section: Notch Signaling In Cutaneous Squamous Cell Carcinoma (Cscc)mentioning
confidence: 99%
“…SFKs, including Fyn, are regulators of cell proliferation, invasion, and metastasis and have been shown to play a role in the pathogenesis of cSCC (29,61,(63)(64)(65). Src-activating and signaling molecule (Srcasm) is a substrate and negative regulator of SFKs (66,67).…”
Section: Pathophysiologic Features Of Csccs Ras Family Members Of Prmentioning
confidence: 99%
“…Invasive SCC is associated with UV-induced mutations in the p53 tumor suppressor gene, 4 Ras activation, NF-B blockade 5 and activation of Src family kinases. 6 However, these factors do not constitute a clear-cut cause or diagnostic or prognostic indicators of tumor aggressiveness. Consequently, there is a continuing need for the identification of target genes or pathways that are relevant to the molecular pathogenesis of SCC.…”
mentioning
confidence: 99%